LACK OF SIZE-ASSORTATIVE MATING IN A WIDESPREAD TREEFROG: PSEUDACRIS CRUCIFER IN IOWA - Moran, Maddox; La Rosa, Emily; Hughes, Daniel (Journal of North American Herpetology, 2024)
The Spring Peeper (Pseudacris crucifer) is a small treefrog native to much of the Central and Eastern USA. Here, we tested if Spring Peepers exhibit size-assortative mating—non-random mate pairings based on body size—from a population in eastern Iowa. We captured 75 amplecting pairs of Spring Peepers during the 2021 breeding season, measured their body sizes, and marked them for future recognition. We found that while sexual-size dimorphism exists between males and females, there was no evidence for size-assortative mating among amplectant pairs. Our study contributes to other recent work indicating that size-assortative mating is rare among most anurans, and that previous findings of this phenomenon in frogs should be interpreted with caution.